Risk Factors Associated With Renal and Urinary Tract Anomalies Delineated by an Ultrasound Screening Program in Infants - Liu, Yuling; Shi, Hua; Yu, Xiaojing; Xiang, Tianchao; Fang, Ye; Xie, Xian; Pan, Xiaofen; Li, Xiaolin; Sun, Zhicai; Zhang, Bihong; Fu, Simao; Rao, Jia (Frontiers in Pediatrics, 2022)
Objective: To evaluate the value of ultrasound screening for congenital anomalies of the kidney and urinary tract (CAKUT) during the early postnatal period. Methods: A prospective study that enrolled all neonates born from August 2019 to July 2020 at one medical center. Postnatal ultrasound screening was conducted in all neonates at 1-month old, 3-month old and 6-month old, respectively. Information on antenatal detection and pregnancy was collected. We performed logistic regression analyses and establish a predictive model to assess the potential risk factors of abnormal ultrasound screening results. Results: Postnatal ultrasound scanning in 4877 infants identified 268 cases (5.5%) of anomalies of kidney and urinary tract by primary screening and 92 cases (1.9%) by tertiary screening. A specific diagnosis was identified in 47 cases within the six-month screening and follow-up program. Logistic regression revealed the preterm birth, oligohydramnios, antenatal ultrasound screening anomalies and gestational hypothyroidism were independent risk factors for early detection of CAKUT by postnatal ultrasound screening. The above factors were adopted to develop a predictive model that showed good calibration in predicting ultrasound findings of CAKUT. Decision curve analysis demonstrated good clinical utility. Conclusions: Postnatal ultrasound screening should be conducted in infants with risk factors associated with CAKUT. Further study on prenatal and fetal factors could help establish the predictive model for early detection of CAKUT.